STRATEGI PERLAWANAN PETANI LAHAN PANTAI MENOLAK PENAMBANGAN PASIR BESI DI KULON PROGO - , ROSTAMIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine more deeply about the resistance movement in the coastal land peasant refuse iron sand mining in Kulon Progo. Peasant are supposed to support the iron sand mining as it aims to improve the welfare of society, but in fact against the mining project. Various attempts were made farmers PPLP resistance to thwart the iron sand mining and until now the fight continues. To sustain their resistance build peasant resistance movement to coordinate, initiate and organize resistance strategy. Looking at the background of the problem of the forms of peasant resistance above, it can be drawn the research question , how collective action is used as a strategy of resistance Land Coastal Farmers Association of Kulon Progo ( PPLP - KP ) in rejecting the iron sand mining? From the basic research question, it can be reduced to the forms of resistance are the farmers? The method used to obtain the data by using qualitative descriptive approach. Data collection techniques to make observations not involved, conduct in-depth interviews, and document study. The goal is to find the data associated with the movement of peasant resistance. Research data were analyzed with the concept of social movements and collective action. The results describe the resistance of peasant in the timeframe of 2006 to 2012. Peasant resistance is mostly done through collective action through protests, demonstrations against the iron sand mining and government. Resistance strategies farmers also utilize political opportunities, political actors seeking support and legal advocacy. This study concluded that the resistance movement represents peasant resistance PPLP marginalized communities against the expansion of foreign corporations that work with the state to economic interests. Peasant also indicated strong resistance of social movements as a control against public policy.